A numerical study of droplet splitting in branched T-shaped microchannel using the two-phase level-set method - Mohammad Raad (SAGE Publishing, 2021)
Droplet splitting as a significant feature of droplet-based microfluidic systems has been widely employed in biotechnology, biomedical engineering, tissue engineering, and it has been preferred over continuous flow systems. In the present paper, two-dimensional numerical simulations have been done to examine the asymmetrical droplet splitting process. The two-phase level set method (LSM) has been predicted to analyze the mechanism of droplet formation and droplet splitting in immiscible liquid/liquid two-phase flow in the branched T-junction microchannel. Governing equations on flow field have been discretized and solved using finite element-based COMSOL Multiphysics software (version 5.3a). Obtained numerical results were validated by experimental data reported in the literature which show acceptable agreement. The model was developed to simulate the mechanism of droplet splitting at the branched T-junction microchannel. This study provides a passive technique to asymmetrically split up microdroplets at the downstream T-junctions. The results show that outlet branches’ pressure gradient affects the droplet splitting. Specifically, it has been shown that the splitting ratio increases by increasing the length ratio, and equal droplet splitting can be achieved where the ratio is L L / L u  = 1. We have used two outlet branches having the same width but different lengths to create the required pressure gradient. As the length ratio of the outlet branches increases, the diameter ratio increases as well.